Aplikasi Beberapa Dosis Formulasi Trichokompos Berbasis Limbah Sawit Dengan Penambahan Nutrisi Pada Bibit Okulasi Karet (Hevea brasiliensis) di Medium Gambut - Silaban, Lina Rita; Puspita, Fifi; ', Sampoerno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine influence the dose formulations based Trichokompos based waste palm oil and get a dose of the best of the gum grafting seedling growth in peat medium. This research was conducted in the experimental fields of the Faculty of Agriculture Crops Laboratory, University of Riau in 6 months from May 2013 to November 2013. Research using Completely Randomized Design (CRD) non-factorial consisting of 5 treatments and 4 replications, each unit consisting of 2 seed. Data were analyzed statistically using analysis of variance and regression analysis Orthogonal Polynomial at 5% level. Parameters measured were seedling height increment, in the number of leaves, stem circumference, dry weight, and the ratio of crown roots. The results showed that application multiple doses of formulations Trichokompos rubber grafting on seedlings significant effect on seedling height increment, the number of leaf and the ratio of crown roots and no real effect on stem circumference and dry weight of seedlings. The optimum dose at intervals no treatment. Keywords : Trichokompos, Dose, Seed Grafting Rubber